RANCANG BANGUN KINCIR AIR SEBAGAI TENAGA PENGGERAK POMPA - Ismanto, Dodi; Trinofrandesta, Edward; Hamid, Hefri (Program Kreativitas Mahasiswa - Teknologi, 2014)
One of the areas that have the potential untapped river water that is in Nagari Padang West Sumatra Ganting Tanah Datar. This area has a rain-fed agricultural land and cultivation can only 1 time in a year, but often failed harvests due to erratic rainfall while irrigated land can grow crops three times a year. From this condition held a mill that is capable of moving the pump to supply the water needs of rainfed rice fields of society. The method used in problem solving is to design a water wheel pump screw propulsion is environmentally friendly. Planning windmill was adapted to the potential presence of the surrounding area. Utilization of river water into a precision that is possible. Before it is delivered to the public for use in the first trial feasibility. From this activity, the target achievement is a model tool that can irrigate agricultural land to grow crops such as paddy rice 1 hectare to 5 hours of operating time / day (without the help of rain). The results of this turbine design produces water flow capacity that can be pumped by 40 ltr / min, with a torque power large enough to dimamfaatkan propulsion pump with a constant flow rate of an average of 5 m / sec. Pump shaft rotation by comparison magnified 5 times to 1500 rpm. Turbine output shaft rotation on average 550 rpm. This screw waterwheel can work continuously so that the pump can be driven over the wheel rotates. With this condition the water being pumped continuously irrigate the fields which are in terrain height of the elevation angle of 300 and a high-lift can reach 10 m.Keywords: water mill, screw, discharge, planning